Beyond Coordinates: Exploring Street Naming Practices in Contemporary Ukraine - Orysia Vira (Colloquia Humanistica)
The paper examines street naming practices in contemporary Ukraine, focusing on the complexity and cultural significance of toponymic changes. In the wake of the Revolution of Dignity and the Russo-Ukrainian War, decommunization gained momentum, changing the names of streets from the Soviet period. The study employs a qualitative approach, is based on document analysis, and presents the case study of historical street names in Lviv as an example. Particular attention is given to Lviv, where a comprehensive dataset of historical street names from the 14th to the 18th centuries has been compiled and presented on an interactive web map. This map not only showcases valuable toponymic data but also contributes to public engagement and promotes the city’s heritage. The study highlights the multifaceted consequences of street renaming. By examining theoretical frameworks of onomastics, urban studies, and cultural geography, it contributes to interdisciplinary discourses on naming studies. Ultimately, it advocates for a holistic approach that harmoniously combines modern realities with historical traditions, ensuring the preservation of cultural identity while considering societal transformations.